The structure and seismicity of Icelandic rifts - Green, Robert George (Department of Earth Sciences, 2017)
Three-fifths of the Earth’s crust has been built at oceanic spreading centres in the last 160 million years. To explore crustal extension processes and the architecture of these constructive plate boundaries I have studied the oceanic rift in Iceland. Here the Mid Atlantic Ridge is anomalously elevated above sea level and thus easier to instrument. I have deployed and operated a dense network of seismometers in the remote volcanic highlands in central Iceland, and used the passive seismic data collected from this network to explore crustal structure and volcanic processes in the extensional rift zones. My analysis of persistent seismicity located in an intervening region between individual spreading segments, uniquely records the segmentation of plate spreading on the scale of individual volcanic systems. Precise location and characterisation of micro-earthquakes identifies a series of faults subparallel to the rift fabric, and source mechanisms define left-lateral strike-slip motion on these faults. This extremely high quality microseismic data reveals transform motion being accommodated by bookshelf faulting in a concentrated region between two such volcanic systems, providing evidence for the localisation of spreading in the discrete volcanic systems. While transform motion between spreading centres appears to be accommodated on a continuous basis, the extension of the brittle upper crust within the spreading centres occurs episodically during rifting events. Our local seismic network fortuitously recorded such a rifting episode in August 2014, during which the opening of a 5 metre wide dyke triggered a huge increase in seismicity across large areas of the rift zone. Stress-seismicity-rate modelling of this triggered seismicity, along with geodetic constraints on the deformation, provided a remarkable opportunity with which it was possible to prove the existence of stress-shadowing, a challenge which has eluded earthquake seismologists for decades. Using the excellent coverage of our extended seismic network ...